2022
DOI: 10.1186/s40795-022-00603-x
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of undernutrition and associated factors among adolescent girls and young women in Ethiopia

Abstract: Background The consequences of undernutrition have serious implication for the health and future reproductive periods of adolescent girls and young women aged 15–24 years. Inspite of this, they are neglected age groups and there is limited information about the nutritional status of this age group in Ethiopia. Therefore, estimating the extent and associated factors of undernutrition among adolescent girls and young women in a national context using multilevel analysis is essential. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…It is interesting to note that women in the poorest wealth index were less likely to be stunted compared to women in the middle wealth index (Table 2). This nding contradicts many studies conducted in other African countries where stunting is more prevalent among women in the poorest wealth indices 30,36,43 .…”
Section: Discussioncontrasting
confidence: 93%
“…It is interesting to note that women in the poorest wealth index were less likely to be stunted compared to women in the middle wealth index (Table 2). This nding contradicts many studies conducted in other African countries where stunting is more prevalent among women in the poorest wealth indices 30,36,43 .…”
Section: Discussioncontrasting
confidence: 93%
“…In which all the aforementioned factors made an impact on their psychology. Tis in turn afects their evaluation of health system responsiveness [56]. Te fnding implies an ongoing health facility reform intending to address nonclinical aspects of rural patients.…”
Section: Factors Associated Withmentioning
confidence: 99%
“…Even if increasing knowledge and attitude scores of HIV-AIDS do not necessarily relate to the actual prevention of HIV-AIDS practices, some studies have found a correlation between HIV-AIDS knowledge and behavior change. (Hong et al, 2012;Kesumawati, 2019;Nwokolo et al, 2011;Shewarega et al, 2022;Swenson et al, 2010). With increased knowledge of HIV-AIDS, students were expected to avoid high-risk behaviors related to HIV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge-based behavior is preferable to unknowledgebased behavior. Because a person's attitude is related to his knowledge, if he lacks knowledge about how to prevent HIV-AIDS transmission, he will likely be unable to do so (Shewarega et al, 2022;Swenson et al, 2010). In addition, ignorance increases the likelihood of believing in HIV-AIDS hoaxes and myths, which contributes to the stigmatization of People Living with HIV (PLHIV) (Sallam et al, 2022;Sen et al, 2021;Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%